2009
DOI: 10.3168/jds.2008-1843
|View full text |Cite
|
Sign up to set email alerts
|

Feeding saponin-containing Yucca schidigera and Quillaja saponaria to decrease enteric methane production in dairy cows

Abstract: An experiment was conducted in vitro to determine whether the addition of saponin-containing Yucca schidigera or Quillaja saponaria reduces methane production without impairing ruminal fermentation or fiber digestion. A slightly lower dose of saponin was then fed to lactating dairy cows to evaluate effects on ruminal fermentation, methane production, total-tract nutrient digestibility, and milk production and composition. A 24-h batch culture in vitro incubation was conducted in a completely randomized design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
135
3
16

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(171 citation statements)
references
References 47 publications
17
135
3
16
Order By: Relevance
“…This cholesterol-reducing effect is attributed to saponins ability to form insoluble complexes (micelles) with sterols (Sidhu and Oakenfull, 1986), such as cholesterol and bile acids. Several feedstuff used for livestock feeding, such as Yucca schidigera (Singer et al, 2008;Holtshausen et al, 2009), Quillaja saponaria (Holtshausen et al, 2009), Medicago sativa (Klita et al, 1996) and Sapindus saponaria (Abreu et al, 2004) contain saponins and are used in -E-mail: vvasta@unict.it animal nutrition with the purpose of inhibiting methanogenesis in the rumen (Patra and Saxena, 2010). Some studies have shown that saponins can be degraded by ruminal microflora (Gutierrez et al, 1959;Makkar and Becker, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This cholesterol-reducing effect is attributed to saponins ability to form insoluble complexes (micelles) with sterols (Sidhu and Oakenfull, 1986), such as cholesterol and bile acids. Several feedstuff used for livestock feeding, such as Yucca schidigera (Singer et al, 2008;Holtshausen et al, 2009), Quillaja saponaria (Holtshausen et al, 2009), Medicago sativa (Klita et al, 1996) and Sapindus saponaria (Abreu et al, 2004) contain saponins and are used in -E-mail: vvasta@unict.it animal nutrition with the purpose of inhibiting methanogenesis in the rumen (Patra and Saxena, 2010). Some studies have shown that saponins can be degraded by ruminal microflora (Gutierrez et al, 1959;Makkar and Becker, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The structures of saponins and their varying proportions from different sources of the same plant material may elicit different responses on rumen metabolism. Also the method of saponin estimation in the extract or plant may differ (12) , which may explain the differences in response of saponins despite similar dose levels (25) . For example, Hostettmann & Marston (15) discussed that spectrophotometric methods are very sensitive, but not suitable for estimation of saponins in crude plant extracts, since colour reactions are not specific, and coloured products may form with phytosterols and flavonoids extracted with saponins.…”
Section: Explaining the Effects Of Saponins On Micro-organismsmentioning
confidence: 99%
“…QS extract (10 %) Heifers 8 91: (24) QS plant (3 %) Dairy cows 10 51:49 (25) Sapindus saponaria fruit Sheep 8 g/kg BW…”
Section: Saponins As Rumen Modifiers In Ruminants 205mentioning
confidence: 99%
“…The effects of Yucca schidigera powder added to lamb ration on rumen total protozoa number and pH, (mean ± SEM), (n=8). Yucca schidigera'nın rumen pH'sı üzerine etkisi, kullanılan dozuna ve ölçümün yapıldığı zamana göre değişkenlik göstermektedir (23,24). Bu çalışmada yem verildikten sonraki 2. saatte YS100 grubunun rumen pH'sı K grubuna göre önemli derecede yüksek bulunurken, diğer zamanlarda gruplar arasında fark olmadığı görülmüştür (Tablo 3).…”
Section: Rumen Ph Değerleriunclassified
“…Konu ile ilgili yapılan çalışmalar bir bütün olarak değerlendirildiğinde Yucca schidigera'nın düşük pH'yı yükselttiği (19,28) veya yüksek pH'yı düşürdüğü görülmektedir (8,27). Ayrıca, Yucca schidigera'nın rumen pH'sı üzerine etkisinin farklı olması rumen ortamının zamanla yemlere uyum sağladığını ve etkilerinin rasyondaki oranı ile ilişkili olduğunu göstermektedir (24).…”
Section: Rumen Ph Değerleriunclassified